Factors Affecting Online Hotel Reservations Intention among Customers in Algeria- Empirical Study - Bouabdellah, hafida (Finance and Business Economies Review, 2020)
The revolution use of information technology and the Internet has contributed significantly to increase the popularity of online shopping as a form of e-commerce. The aim of this research is to determine important factors that are associated with online hotel reservation intention among customers. The questionnaires were used to collect the primary data, and 74 respondents are selected by convenience sample. The research concluded that are ten factors were significantly associated with online hotel reservation intention, among them are: (1) reliability of information published; (2) reduced perceived risk; (3) satisfaction with past experience; (4) the credibility of travel and tourism agencies; (5) low prices: and (6) easy access to hotel information. Finally, we suggest some recommendations for hotel managers to help them increase online hotel reservations. Online; Reservations; Purchasing Intention; Customer; Hotels.